China's global strategy : towards a multipolar world - Clegg, Jenny (Pluto Press ; Distributed in the United States of America exclusively by Palgrave Macmillan, 2009)
"China is fast emerging as a powerful player on the world stage. This book takes a closer look at the country's stance on a range of global issues, arguing that its multipolar diplomacy offers a concrete strategy to constrain the US pursuit of unipolar primacy. Many people assume that China will follow an imperialistic strategy and therefore be in direct conflict with the American empire in a quest for world domination. Jenny Clegg shows that China is in fact taking a multilateral approach, offering real assistance to developing countries and helping to build the institutions required to run a multipolar world. Without glossing over China's own internal difficulties, the book argues that its international consensus-building strategy could lead to a more peaceful and equitable world. This book offers a refreshing perspective on China that will be of great value to those interested in the big political questions of how to tackle war and imperialism, globalisation and development as well as to undergraduate students of politics, economics and international relations."--Publisher description